Burden of falls attributable to low bone mineral density among people aged 60 years and over in China from 1990 to 2019 - Fu, Yali; Ba, Lei; Lü, Nianqing; Yang, Huafeng; Hong, Xin; Zhou, Jinyi; Sun, Zhiming (Frontiers in Public Health, 2023)
Objective: Falls in older people have become a major public health, economic and societal problem. Osteoporosis predisposes older adults to high risk of falls, which were the most common outcome attributable to low bone mineral density (LBMD). In this study, we analyze the long-term trends in falls burden attributable to LBMD among people aged 60 years and over from 1990 to 2019, using data from the Global Burden of Diseases, Injuries, and Risk Factors Study 2019 (GBD 2019) . Methods: Data from GBD 2019 were used to assess the long-term trends in mortality and disability-adjusted life-year (DALY) rates by Joinpoint regression. The age-period-cohort (APC) model was used to evaluate the effects of age, period and cohort on mortality rate of falls attributable to LBMD. Results: The mortality and DALYs rates of falls attributable to LBMD among people aged 60 years and over increased from 1990 to 2019, with average annual percentage changes (AAPCs) of 1.74% (95% CI: -1.47% to 2.01%) and 0.99% (95% CI: 0.80% to 1.19%), respectively. APC analysis revealed that the mortality rate due to LBMD significantly increased among the elderly over the age of 75 years. The risk of falls mortality due to LBMD during the period of 1990 to 2019 initially declined but later elevated. An overall increasing risk for falls death attributable to LBMD was presented across birth cohorts, but in cohorts born after 1930, the upward trend has slowed down. The overall net drift per year attributable to LBMD was above 0. The corresponding results showed that the negative impact of period and cohort effects among males was more pronounced than those among females. Conclusions: Falls attributable to LBMD remain an ongoing health burden in the elderly in China, and the mortality has been on the rise from 1990 to 2019, especially among the elderly aged 80+ years group. The prevention and treatment of LBMD should be emphasized, especially among males and oldest-old people. Furthermore, there is an urgent need to strengthen the implementation of system-wide, integrated and effective public health policies and other health interventions in China.